Technological Advances and the Future of Suicide Prevention: Ethical, Legal, and Empirical Challenges. Issue 3 (5th December 2019) - Berman, Alan L.; Carter, Gregory
Abstract : Technological advancements have brought multiple and diverse benefits to our human existence. In suicide prevention, new technologies have spurred great interest in and reports of the applicability to assessing, monitoring, and intervening in various community and clinical populations. We argue in this article that we need to better understand the complexities of implementation of technological advances; especially the accuracy, effectiveness, safety, ethical, and legal issues, even as implementation occurs at individual, clinical, and population levels, in order to achieve that measure of public health impact we all desire (i.e., greater benefit than harm).